Internalization of 'Panca Jiwa Pondok' in Pesantren: An Ethnomethodological Study - Nurul Fitriyah A.W; Rahmatullah, Azam Syukur; Othman, Mohd Sukki (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to explore a deep understanding of the internalization of the five principles of the Pesantren among all stakeholders, especially the students. Another goal is to explore the essence and implementation of the Panca Jiwa Pondok of the Pesantren that have been initiated by the founders of Pondok Pesantren Gontor in Ponorogo, East Java, and how Gontor alums and non-alumni boarding schools adopt this. Design/methods/approach – This research uses a qualitative method with an ethnomethodological approach. This method focuses on the resources, procedures, and practices that group or community members use to produce and recognize social realities that can be sensed. The research was conducted at Al Kamal Islamic Boarding School in Tambaksari Kuwarasan, Kebumen, Indonesia. Data was collected through natural interviews in daily life involving researchers in the pesantren environment. The data analysis process was conducted descriptively since the first data collection, so it did not wait for excessive data accumulation. Findings – This research reveals three main characteristics of the Panca Jiwa Pondok: strengthening of social piety, strengthening of intrapersonal aspects, and spirituality. The internalization process of